Studies on biotransformation mechanism of Fusarium sp. C39 to enhance saponin content of Paridis Rhizoma - Chen, Yiyang; Yu, Dan; Huo, Jinhai; Huang, Nannan; Zhang, Meng; Du, Xiaowei (Frontiers in Microbiology, 2022)
Paridis Rhizoma is a natural medicine with strong anti-tumor and anti-inflammatory activities. Our previous research have found that Fusarium sp. C39, an endophytic fungus isolated from Dioscorea nipponica which contains the similar chemical components, significantly increased the steroidal saponins content of Paridis Rhizoma by fermentation. In this study, the inhibitory effects of fermentated Paridis Rhizoma extract (PRE) on liver cancer cells (Hepal-6), cervical cancer cells (Hela), and lung cancer cells (A549) were determined to be stronger than that of the unfermented extract. For discovering the fermentation mechanism of PRE with Fusarium sp. C39, 36 components with obviously quantitative variations were screened out by UPLC-Q/TOF-MS and 53 key genes involved in the metabolic pathways of steroidal saponins were identified by transcriptome. On the basis of comprehensively analysing information from the metabonomics and transcriptome, it can be speculated that the increase of spirostanol saponins and nuatigenin-type saponins enhanced the inhibitory effect of fermented PRE on cancer cell proliferation. Under the action of glycosidase, glycosyltransferase, oxidoreductases, and genes involved in sterol synthesis, strain C39 achieved the synthesis of diosgenin and the alteration of configurations, sugar chain and substituent of steroidal saponins. The research suggested a microbial transformation approach to increase the resource utilization and activity of Paris polyphylla.